Implementation of Ecommerce on Small and Medium Enterprise - Tugiman Tugiman; Dellih Wijaya; Yakub Yakub (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
The trend of information system development and technological developments is continuously increasing. Every person or business actor must continuously update the technology. Based on the published results of a survey conducted by Indonesian Internet Service Providers Association at the end of 2018, internet users in Indonesia reached 171.17 million from 264.16 million people or 64.8% of the total population.. Related to this, the researchers conducted research on the implementation of e-commerce in Small and Medium Enterprise. Testing of this study uses the User Acceptance Test. The method that the authors do is by making a system that is applied to Small and Medium Enterprise. Untuk mengetahui mengenai penerimaan sistem dan kegunaannya yang berkaitan dengan e-commerce penulis menggunakan metode kuesioner. Based on the black box examiner all test results show valid, while the examiner using the User Acceptance Test produces a number of 80.5% with good criteria. The answers used in this study may be 39 people